To compare the functions \( f(x) = x^3 + 1 \) and \( g(x) = x + 1 \) and to analyze their intercepts, let’s calculate their x-intercepts and y-intercepts.
Finding the intercepts
-
y-intercept: This is found by evaluating the function at \( x = 0 \).
-
For \( f(x) \): \[ f(0) = 0^3 + 1 = 1 \] So the y-intercept of \( f(x) \) is \( (0, 1) \).
-
For \( g(x) \): \[ g(0) = 0 + 1 = 1 \] So the y-intercept of \( g(x) \) is also \( (0, 1) \).
-
-
x-intercept: This is found by evaluating the function when \( f(x) = 0 \) or \( g(x) = 0 \).
-
For \( f(x) \): \[ x^3 + 1 = 0 \implies x^3 = -1 \implies x = -1 \] So the x-intercept of \( f(x) \) is \( (-1, 0) \).
-
For \( g(x) \): \[ x + 1 = 0 \implies x = -1 \] So the x-intercept of \( g(x) \) is \( (-1, 0) \).
-
Summary of intercepts
- Both functions have a y-intercept of \( (0, 1) \).
- Both functions have an x-intercept of \( (-1, 0) \).
Conclusion
The statement that both functions have an x-intercept of \( (-1, 0) \) and a y-intercept of \( (0, 1) \) is true. Therefore, the correct response is:
Both functions have an x-intercept of (−1,0) and a y-intercept of (0,1).